Sam Wu is NOT afraid of ghosts - Tsang, Katie, 1987-; Tsang, Kevin (Tsang, Katie, 1987- Sam Wu is not afraid., 2018)
After an embarrassing incident on his school field trip, Sam is determined to prove that he is not afraid of ghosts.